Determination of Copper, Cobalt, Cadmium, Lead, Nickel and Chromium by Atomic Absorption Spectrometry in Bottled Minerals Water from Turkey after Preconcentration/Separation in Activated Carbon - Soylak, M.; Narin, I.; Elci, L.; Dogan, M. (Asian Journal of Chemistry, 2010)
Copper, cobalt, cadmium, lead, nickel and chromium concentrations were determined in some bottled mineral water samples purchased from local markets in Nigde and Kayseri-Turkey by atomic absorption spectrometry after preconcentration/separation procedure on the activated carbon column as pyrocatechol violet complexes. The concentration ranges of copper, cobalt, chromium, lead and nickel were found to be as 10.3-37.4 μg/L, 2.0-2.3 μg/L, 2.0-4.6 μg/L, 2.0-3.4 μg/L 4.7-16.7 μg/L respectively. The cadmium concentrations of all the samples were found to be below 0.1 μg/L.